Effects of Pre-Pregnancy Body Mass Index and Gestational Weight Gain on Low Birth Weight in Omani Infants : A case-control study - Mustafa Al-Hinai; Majid Al-Muqbali; Aisha Al-Moqbali; Vaidyanathan Gowri; Abdullah Al-Maniri (Sultan Qaboos University Medical Journal, 2013)
Objectives: This study aimed to investigate the association between pre-pregnancy maternal body mass index (BMI), gestational weight gain and low birth weight (LBW) in babies born to a sample population of Omani women. Methods: A case-control study was carried out among deliveries registered between 1st May 2010 and 30th April 2011 at Sultan Qaboos University Hospital, Muscat, Oman. A case was defined as a woman who delivered a low birth weight baby (<2,500 g); a control was a woman delivering a baby weighing between 2,500 and 4,000 g. A random selection of 150 cases and 300 controls was carried out using the hospital information system. Maternal, pre-natal, and delivery data were extracted from the mothers’ follow-up cards. Bivariate and multivariate logistic regression analyses were executed to examine the association between pre-pregnancy maternal BMI and LBW. Results: The percentage of underweight mothers (BMI <18.5) was higher among the cases compared to the controls (17.3% versus 6%; P <0.001). The proportion of mothers with less-than-recommended weight gain was also higher among the cases compared to the controls (57.7% versus 33%; P <0.001). After adjustment for potential confounders, infants of underweight mothers had more than twice the risk of LBW compared to those of mothers with normal weight (odds ratio = 2.27; 95% confidence interval 1.09–4.71). Conclusion: Underweight Omani women as well as women with less-than-recommended gestational weight gain were at higher risk of delivering LBW babies. Maternal health promotion programmes should be directed towards improving mothers’ nutrition before and during pregnancies.